ChemInform Abstract: Synthesis of N‐Aryl Imidazoles Catalyzed by Copper Nanoparticles on Nanosized Silica‐Coated Maghemite. Issue 4 (January 2015) - Nador, Fabiana; Volpe, Maria Alicia; Alonso, Francisco; Radivoy, Gabriel
Abstract Aryl chlorides are almost unreactive under the investigated conditions allowing the selective monoarylation of chloroiodobenzene.